Investigating the Concept of Authenticity in Restoration in Light of Archive Documents: Kayseri Sahabiye Madrasah - Ayşegül Akşehirlioğlu (Art-Sanat)
The desire and necessity of civilizations to preserve their cultural identities have led to the concept of architectural conservation, which has evolved and changed over time. Many conservation criteria have been defined within this context. Nowadays, the primary goal of conservation efforts is the conservation of cultural heritage’s authentic qualities and components and convey them to future generations. Sahabiye Madrasah, constructed in 1267-1268 by Sahip Ata Fahreddin Ali in Kayseri, is one of the significant structures of the Seljuk Period, and it owes its current presence mainly to the conservation activities it has undergone over time. In this study, the concept of authenticity in conservation is questioned, and a historical and architectural description of the madrasah is provided. Archive research was conducted to trace the repairs carried out during the Ottoman and Republic periods, and by making use of the data obtained, maintenance and repair operations are listed in chronological order. Information gaps in the structure’s conservation history are explained by using the relevant documents, and the approach to authenticity in conservation during the period of conservation intervention is questioned by considering the effective authorities, actors, and theoretical, technical, legal, and administrative functioning in practice. This study, which examines the concept of authenticity in the restoration process of Sahabiye Madrasah, analyzes the structure’s restoration problems and current condition based on the idea of authenticity as defined in international texts, considering the conditions of the relevant period. From this aspect, this significant medieval monumental structure, which has been addressed many times in various contexts, is discussed for the first time in its restoration history and the issue of authenticity, to provide a substantial foundation for future research and guiding and enlightening future studies.